Researching youth voices on Comprehensive Sexuality Education: A literature review of qualitative studies - Carolina Trivelli Diaz (Encyclopaideia)
The past decades have seen an increase in the design and implementation of sexuality education programs deemed comprehensive within formal schooling. Qualitative research is gaining relevance in the field; however, few studies focus on youth perspectives. This study analyzes qualitative research through a literature review on the implementation of Comprehensive Sexuality Education (CSE) programs from the perspective of young people. A review of qualitative studies and a meta-synthesis were conducted to outline a state-of-the-art of qualitative research on youth perceptions of CSE. Results point to two main areas of concern for youth: contents and pedagogy. There remains a general dissatisfaction over the depth and breadth of the CSE curriculum, leaving young people feeling unprepared for positive relationships and good sexual health. In terms of pedagogy, there is still a shortfall in the effective implementation of innovative teaching and learning strategies, pointing towards a gap regarding the pedagogical frameworks underlying CSE.